Empowerement of the Community in the Construction of a Concrete Bridge in Bahari Village, Wotu Sub-District, East Luwu District - Rahmad Rahmad; Hairuddin Hairuddin; Adnan Adnan (Journal of Social Entrepreneurship and Creative Technology, 2024)
East Luwu Regency is one of the Second Level Regions in the province of South Sulawesi, Indonesia. The regency originated from the expansion of North Luwu Regency which was passed by Law No. 7/2003 on 25 February 2003. Malili is the capital city of East Luwu Regency, located at the northern end of the Gulf of Bone. community engagement ensures the long-term success of bridge projects. By empowering communities, fostering transparency, and considering social and economic factors, we can build bridges that truly benefit everyone.